Development of perovskite-based light emitting diodes with improved stability 6.0 - Lok, Weng Kiat (2019)
The all-inorganic colloidal CsPbX3, (X = Cl, Br, I) nanocrystals are being studied broadly as a new candidate of optoelectronic material because of its tunable wavelength and high photoluminescence quantum yield (PL QY). Nevertheless, the instability of the nanocrystals due to the delocalisation of ions hinder the application. Changing the surface ligands used to synthesise the perovskite quantum dots (PQDs) is a straightforward and workable method. The oleylamine (OLA) is the classic ligands used in the hot-injection synthesis process. Hence, the (3-aminopropyl) triethoxysilane (APTES) is proposed as the new surface ligand to address the stability issue.